(untitled) (Eurasian Medical Research Periodical, 2022)
The present study focuses on 104 patients with differentiated connective tissue dysplasia (DCTD) (Marfan syndrome) and undifferentiated connective tissue dysplasia (UDCTD). General clinical investigations - questioning, physical examination, instrumental, biochemical, and chemoluminescent procedures were used.